Why Do Fund Managers Identify and Share Profitable Ideas? - Crawford, Steven S.; Gray, Wesley R.; Kern, Andrew E. (Journal of Financial and Quantitative Analysis, 2017)
We study data from an organization in which fund managers privately share and discuss detailed investment recommendations. Buy recommendations generate positive abnormal returns, and sell recommendations result in negative abnormal returns. In the context of these results, we explore an important economic question: Why do skilled investors share profitable ideas with others? Evidence suggests that the managers in our sample share to receive feedback on their ideas and to attract additional arbitrageur capital to the securities they recommend in order to correct mispricings.